Determinants of Capital Structure of IT Listed Firms: Comparative Evidence from China and India - WU, JINGWEN (2017)
ABSTRACT Purpose – This thesis explores the firm-specific factors that impact the capital structures of IT listed companies in China and India during the ten- year period from 2006 to 2015 and make a comparison between China and India, and to examine whether the capital structure theories derived from western countries can provide much better explanations for the capital structure decisions of IT listed companies in China and India.